Identifying Topics and Difficulties on Collaboration in Social Innovation Environments - Pinheiro, Mariana Cardoso; Chueri, Luciana de Oliveira Vilanova; Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de Informação, 2020)
There are currently several social innovation initiatives being developed in isolation, where each one has its own path. In this context, actors want to collaborate and be coordinated in a network in order to increase the development and dissemination of social innovations. The use of collaboration mechanisms gives rise to the expectation that actors playing in groups tend to achieve quantitative and qualitative performance higher than individual performances. While the potential benefits of collaboration are recognized, effectively achieving collaboration is still a challenge for social innovation. In this context, the objective of this study is to identify how the concepts of collaboration are recognized in social innovation environments. In addition, we investigated which mechanisms are used and what are the difficulties faced by actors in this context. To do so, a survey research on the aspects of collaboration in social innovation environments was conducted. Results shown that engagement is the most cited challenge related to human factors; from 30 techniques mentioned, Design Thinking is the most applied; and from 41 tools, Google Drive is the most cited. Results from qualitative analysis shown that collaboration is considered essential to social innovation environments, although there are several challenges reported.